Diversidade de recursos vegetais utilizados em comunidades rurais de Sinop, Mato Grosso, Brasil - Spanholi, Maira Luiza (2016)
Plants are essential for our day to day and because of that because we have used plants for many years to meet our various demands. The study of the relationship between man and plant through ethnobotany is important to rescue the traditional knowledge on the use of plant resources, enabling the transmission of information between generations. Therefore, the objective of this study was to describe the plant resources collected, cultivated, conserved and used by families residing in rural communities in the municipality of Sinop, state of Mato Grosso, in order to systematize and identify their botanical families and to establish a socio - cultural and economic relationship between them. The methodology was based on field survey through free list technique and semi-structured questionnaire and was using the snowball procedure. The communities studied were: Brígida, 11 de Julho, Adalgisa, Agrovila, Planalto, Bom Jardim and Monalisa. 226 people were interviewed and data were analyzed using the software R. The chi-square test and Kruskal-Wallis was used to evaluate if there are differences between native and exotic plants and difference in knowledge between men and women and simple linear regression assessed whether income can explain the number of plants cited. It was determined the use value (UV), informant consensus factor (ICF) and plants fidelity level (FL). 2.885 plants were cited, with 217 species in 70 different botanical families, 66% of these are for food, 31% for medical use and 4% for other uses. The chi-square test revealed that there is no significant difference between the wealth of native and exotic species in the communities studied. The Kruskal Wallis test showed no differences in species citations between gender, age, income and education of the respondents. Mango was the plant with higher UV and ICF (Mangifera indica L.). This demonstrates that people consider this plant as the most important in their daily life, because it is the one with the greatest number of uses, as it is used for food, medicine preparation, shade supply for backyards, among others. Women and people over 51 years old cited the largest amount of plants. In addition, there are plants in gardens that are not used by the residents for lack of knowledge of its properties or its manner of use. It should adopt strategies that encourage young people to be interested, to know and to use the most diverse species of plant resources. Because plants are primordial for a subsistence of the residents of the studied communities, however younger people have stopped using and then the knowledge of plant use form is being lost.